An anti-coagulation glaucoma aqueous humor intra-drainage stent and a preparation method and application thereof

CN122516462BActive Publication Date: 2026-10-16THE EYE HOSPITAL OF WENZHOU MEDICAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611030916.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-16
Estimated Expiration
2046-07-13

AI Technical Summary

Technical Problem

这使得功能性涂层难以与基体形成牢固的化学键合,不仅限制了药物的有效负载量(难以达到治疗阈值),更导致涂层在植入初期极易发生剥离或脱落,引发安全性风险

Benefits of technology

[0019]本发明的有益效果是:本发明提供了一种抗凝青光眼房水内引流支架及其制备方法与应用。该支架以镍钛为基体,依次经电化学抛光和碱热处理形成多孔表面,并通过溶液共沉积技术同步负载贻贝粘蛋白与比伐芦丁,构建分级涂层。相较于现有技术,本发明具有以下显著优势:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122516462B_ABST
    Figure CN122516462B_ABST
Patent Text Reader

Abstract

The application discloses an anti-coagulation glaucoma aqueous humor internal drainage stent and a preparation method and application thereof. The stent is based on a nickel-titanium substrate, the surface of which is sequentially subjected to electrochemical polishing and alkali heat treatment to construct a uniform porous micro-nano structure; on this basis, a hierarchical coating is constructed by adopting a solution co-deposition technology, and the coating is composed of a chemical fixation bottom layer of mussel adhesive protein and a mussel adhesive protein / bivatradin functional surface layer. The application utilizes the excellent interfacial adhesion and anti-inflammatory activity of mussel adhesive protein and the specific anti-coagulation efficacy of bivatradin, and the two exert a synergistic effect on the surface of the stent. Under the premise of ensuring the mechanical stability of the nickel-titanium substrate and the aqueous humor drainage efficiency, the stent can significantly inhibit platelet adhesion and inflammatory cascade reaction and effectively reduce the risk of thrombosis. Compared with a traditional process, the preparation method of the application breaks through the limitation of a multi-step complex surface treatment and is simple and controllable. The obtained stent has the advantages of firm coating combination, excellent biocompatibility and long-term patency and the like, and is not only suitable for minimally invasive treatment of glaucoma, but also can be popularized to other ophthalmic implant instrument fields which have strict requirements on anti-coagulation-anti-inflammatory dual performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical device technology, specifically relating to a nickel-titanium aqueous humor drainage stent with long-lasting anticoagulation and anti-inflammatory functions, and the preparation method and application of its surface functionalized coating. Background Technology

[0002] Glaucoma is one of the leading causes of blindness worldwide, and controlling intraocular pressure is the core strategy for its treatment. As a crucial interventional device, the performance of the aqueous humor drainage system directly determines the success or failure of the surgery. Traditional external drainage devices mostly use high-molecular polymer materials such as silicone. Although their biocompatibility is acceptable, they are prone to inducing postoperative fibrous encapsulation, leading to drainage channel blockage and failure. In recent years, with the rapid development of minimally invasive glaucoma surgery (MIGS), nickel-titanium has become the preferred substrate for novel aqueous humor drainage stents due to its excellent shape memory effect and high radial support. However, in the process of directly constructing an anticoagulant functional coating on the surface of nickel-titanium stents to prevent thrombosis and maintain long-term patency, the following three major technical bottlenecks remain: 1. Weak interfacial bonding leads to limited drug loading and early detachment. The naturally formed oxide layer on the nickel-titanium surface is dense and chemically inert, lacking effective active functional groups. This makes it difficult for functional coatings to form strong chemical bonds with the substrate, which not only limits the effective drug loading (making it difficult to reach the therapeutic threshold) but also makes the coating very prone to peeling or detachment in the early stages of implantation, posing safety risks.

[0003] 2. Technological limitations lead to uneven coating distribution, affecting the consistency of therapeutic efficacy. Existing coating processes struggle to achieve uniform coverage within scaffolds with complex three-dimensional porous structures, often resulting in coating dead zones or significant local thickness differences. This heterogeneity can lead to uncontrolled drug release kinetics (such as burst release or incomplete release), severely impacting the consistency and predictability of clinical efficacy.

[0004] 3. Limited functionality and insufficient long-term stability make them ill-suited to the complex intraocular microenvironment. Most existing coatings possess only a single anticoagulation function, lacking a synergistic "anti-inflammatory-anticoagulation" mechanism, making it difficult to effectively address the complex inflammatory microenvironment within the eye. Furthermore, due to weak interfacial adhesion, the coating is highly susceptible to fatigue peeling under the continuous flushing of aqueous humor and the micro-deformation of the stent during eye movements, leading to premature failure of the long-term anticoagulation function and failing to meet the requirements for long-term implantation. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides an anticoagulation glaucoma aqueous humor drainage stent and its preparation method. This invention employs a "pre-deposition-mixed co-deposition" strategy: utilizing the strong chemical fixation properties of the dopa group in mussel adhesive protein (MAP) and the excellent anticoagulation properties of bivalirudin (Biva), a functional coating with a hierarchical structure is successfully constructed.

[0006] First, a highly active pre-deposited layer was constructed by pre-modifying a nickel-titanium matrix under weakly alkaline conditions using mussel adhesive protein to enhance interfacial bonding. Second, the pre-modified scaffold was immersed in a mixed solution of mussel adhesive protein and bivalirutin. Utilizing the oxidative cross-linking network of dopamine groups and their electrostatic / hydrogen bond interactions with bivalirutin, a uniform and dense mussel adhesive protein / bivalirutin coating was in situ constructed on the pre-deposited layer via a co-deposition process. During this process, bivalirutin molecules were dynamically captured and stably locked within the protein network. Finally, by adjusting the concentration of the precursor solution and reaction conditions, the ratio of the two components in the coating could be flexibly controlled, thereby achieving an optimal balance between anticoagulant properties and biocompatibility.

[0007] This invention provides an intra-aqueous drainage stent for anticoagulation glaucoma and its technical solution: the stent uses nickel-titanium as a substrate, and its surface is treated to form a porous microstructure; the porous structure surface is loaded with a hierarchical coating, which consists of two parts: a bottom layer is a chemical fixation layer formed by pre-deposition of mussel adhesive protein to enhance interfacial bonding; the top layer is a functional layer formed by co-deposition of mussel adhesive protein and bivalirutin in a mixed solution. The two components in the top coating are deposited in a specific mass ratio, which can be flexibly adjusted according to the target drug release kinetics and anticoagulation strength requirements.

[0008] The preparation method of the above-mentioned anticoagulation glaucoma aqueous humor drainage stent includes the following steps: S1. Electrochemical polishing: The nickel-titanium substrate was immersed in a phosphoric acid solution and polished by applying direct current (current density: 0.5-1.5 A / dm², time: 15-20 min) to remove surface processing defects and the original oxide layer. Subsequently, the substrate was ultrasonically cleaned sequentially with anhydrous ethanol and deionized water (frequency: 40 kHz, power: 100 W, 15-30 min each), and finally dried in a vacuum environment for 2 h.

[0009] S2. Alkali Heat Treatment: The polished support was immersed in a sodium hydroxide solution (concentration: 14 wt%, 26 wt%) in a PTFE-lined container for 24 h (temperature: 37℃, 50℃) to generate a hydroxyl-rich nanonetwork structure on the surface. After removal, it was soaked in 0.01-0.1 mol / L dilute hydrochloric acid for 2 h to neutralize the residual alkali and regenerate the surface oxide layer. Finally, it was rinsed three times with deionized water until neutral and then vacuum dried.

[0010] S3. Construction of the mussel adhesive protein pre-deposition layer: Prepare mussel adhesive protein solutions with concentrations of 0.25-1.0 mg / mL (selectable gradients: 0.25, 0.5, 0.75, 1.0 mg / mL) in 10 mM Tris-HCl buffer (pH 8.0). Completely immerse the scaffold treated in step (2) in this solution and allow it to stand at room temperature for 2 h. Mechanism explanation: Utilizing the strong coordination between the dopa groups in mussel adhesive protein and the metal surface, a highly active pre-deposition layer is formed on the scaffold surface, providing a strong chemical fixation site for the subsequent coating growth.

[0011] S4. Co-deposition of mussel adhesive protein / bivalirutin coating: Prepare a mixed solution of mussel adhesive protein and bivalirutin using 10 mM Tris-HCl buffer (pH 8.0) as solvent. By adjusting the initial concentration ratio of the two components, the drug loading density of the final coating can be flexibly controlled (preferably a mass ratio of about 1:1 to balance mechanical properties and anticoagulant effect; the proportion of bivalirutin can also be increased to enhance anticoagulant properties, or the proportion of mussel adhesive protein can be increased to improve coating stability). The scaffold with the pre-deposited layer obtained in step (3) is transferred to this mixed solution and allowed to stand at room temperature for 2 h. Under this weakly alkaline environment, the mussel adhesive protein in the solution undergoes oxidative self-polymerization and forms chemical cross-links with the underlying pre-deposited layer; at the same time, with the help of electrostatic interaction and hydrogen bonding, the bivalirutin molecules are tightly embedded and locked in the in-situ generated protein network, thereby constructing a uniform, high-load mussel adhesive protein / bivalirutin coating.

[0012] S5. Post-processing and finished product preparation: The coated scaffold is washed in deionized water for 24 h to remove unbound free proteins and drug molecules. Subsequently, it is vacuum dried at 37°C for 24 h, or freeze-dried to obtain the final product.

[0013] Detailed parameter descriptions In a preferred embodiment of the present invention, the specific process parameters for manufacturing the anticoagulation glaucoma aqueous humor drainage stent are as follows: In step S1, the concentration of the phosphoric acid solution is 10 wt%, and the processing temperature is 60℃.

[0014] The concentration of the sodium hydroxide solution in step S2 is 26 wt%.

[0015] In step S2, the acid solution concentration is a dilute hydrochloric acid solution with a concentration of 0.01-0.1 mol / L.

[0016] In step S3, the concentration of the pre-deposited bottom layer mussel adhesive protein solution is 0.5 mg / mL.

[0017] In step S4, the mussel adhesive protein / bivalutine mixed solution has a mass concentration ratio of 1:1 and a mass concentration of 0.5 mg / mL for both.

[0018] Application of a mussel adhesive protein / bivalirutin coating in the preparation of ophthalmic anticoagulant and antithrombotic materials.

[0019] The beneficial effects of this invention are as follows: This invention provides an anticoagulation glaucoma aqueous humor drainage stent, its preparation method, and its application. The stent uses a nickel-titanium substrate, which undergoes electrochemical polishing and alkaline heat treatment to form a porous surface. Mussel adhesive protein and bivalirutin are simultaneously loaded using solution co-deposition technology to construct a hierarchical coating. Compared with existing technologies, this invention has the following significant advantages: 1. Synergistic Performance Enhancement: The natural anti-inflammatory properties of mussel adhesive protein and the targeted anticoagulant effect of bivalirutin produce a synergistic effect. Experimental data show (see appendix) Figure 16-21 At a specific ratio (1:1), this coating can significantly reduce the hemolysis rate, effectively inhibit platelet adhesion, scavenge reactive oxygen species (ROS), and greatly prolong the coagulation time (APTT / TT). While maintaining the mechanical stability of the nickel-titanium substrate, it greatly reduces the risk of postoperative inflammatory response and thrombosis.

[0020] 2. Simplified and controllable process: By fixing key parameters (such as 10 wt% phosphoric acid / 60℃ polishing, 26 wt% sodium hydroxide treatment, 0.5 mg / mL mussel adhesive protein pre-deposition, and 1:1 co-deposition), standardized control of coating thickness, drug loading, and release kinetics was achieved. This method effectively solves the problems of large batch-to-batch variations and uneven coating distribution in traditional processes, and has advantages such as environmentally friendly process and low reagent consumption.

[0021] 3. Long-lasting and highly safe: In vivo experiments confirm this (see appendix). Figure 22-27 This coating effectively inhibits thrombus formation and foreign body reaction within Schlemm's canal, reduces macrophage infiltration, and prolongs stent patency life. Furthermore, the functional coating provided by this invention is not only applicable to glaucoma drainage stents but can also be widely used in the preparation of other ophthalmic anticoagulant and antithrombotic materials, such as contact lenses, intraocular implants, and microcatheters, demonstrating broad clinical application prospects. Attached Figure Description

[0022] Figure 1 The scanning electron microscope (SEM) image of the support surface after electrochemical polishing in Example 1 shows that the surface is smooth and burr-free.

[0023] Figure 2 SEM image of the polished support after alkaline heat treatment (14 wt% sodium hydroxide, 37°C) in Example 2.

[0024] Figure 3 SEM image of the polished support after alkaline heat treatment (14 wt% sodium hydroxide, 50°C) in Example 3.

[0025] Figure 4 SEM image of the polished support after alkaline heat treatment (26 wt% sodium hydroxide, 37°C) in Example 4 (preferred embodiment, showing a rich mesh structure).

[0026] Figure 5 SEM image of the polished support after alkaline heat treatment (26 wt% sodium hydroxide, 50°C) in Example 5.

[0027] Figure 6 Example 6: SEM image of the mussel adhesive protein (0.25 mg / mL) coating prepared on the porous surface of the scaffold.

[0028] Figure 7 Example 7: SEM image of mussel adhesive protein (0.5 mg / mL) coating prepared on the porous surface of the scaffold (preferred example, showing the optimal binding layer concentration).

[0029] Figure 8 Example 8: SEM image of the mussel adhesive protein (0.75 mg / mL) coating prepared on the porous surface of the scaffold.

[0030] Figure 9 Example 9: SEM image of the mussel adhesive protein (1.0 mg / mL) coating prepared on the porous surface of the scaffold.

[0031] Figure 10 Example 10: SEM image of the mussel adhesive protein (0.5 mg / mL) / bivalirutin (0.25 mg / mL) coating.

[0032] Figure 11 (A) SEM image of the mussel adhesive protein (0.5 mg / mL) / bivalirutin (0.5 mg / mL) coating prepared in Example 11 (preferred embodiment, showing a uniform and dense coating); (B) MAP of scaffold preparation 0.5 / Biva 0.5 coating.

[0033] Figure 12 Example 12: SEM image of the mussel adhesive protein (0.5 mg / mL) / bivalirutin (0.75 mg / mL) coating.

[0034] Figure 13 Mussel adhesive protein standard curve, used for quantitative analysis of drug loading.

[0035] Figure 14 Bivalirutin standard curve, used for quantitative analysis of drug loading.

[0036] Figure 15 The cumulative release-time curves of mussel adhesive protein and bivalirutin demonstrate the long-acting sustained-release properties of the drugs.

[0037] Figure 16 MAP in Example 15 0.5 / Biva 0.5 The hemolysis rate test results of the coating showed excellent blood compatibility.

[0038] Figure 17 The survival rate of corneal epithelial cells on the coating surface in Example 16 demonstrates good cell compatibility.

[0039] Figure 18 In Example 17, the anticoagulant activity test showed a significant prolongation of clotting time.

[0040] Figure 19 In Example 18, SEM observation of platelet adhesion morphology on the coating surface showed that platelet activation was inhibited.

[0041] Figure 20 In Example 19, the adhesion morphology of whole blood cells on the coating surface was observed by SEM.

[0042] Figure 21 The ROS scavenging ability of the coating in Example 20 was evaluated, demonstrating its antioxidant / anti-inflammatory potential.

[0043] Figure 22 Example 21 shows the SEM comparison images after implantation in vivo, demonstrating the tissue compatibility status, thrombus deposition degree, and coating integrity of the two groups of stents.

[0044] Figure 23 MAP in Example 22 0.5 / Biva 0.5 In vivo anti-inflammatory evaluation of the coating showed a mild inflammatory response.

[0045] Figure 24 In Example 22, in vivo evaluation of macrophage infiltration (F4 / 80 labeling) showed a significant reduction in macrophage aggregation.

[0046] Figure 25 MAP in Example 23 0.5 / Biva 0.5 Evaluation of in vivo anticoagulation after coating implantation in Schlem tubes.

[0047] Figure 26 Pathological sections of the tissue surrounding the implanted Schlem tube in Example 24 showed normal tissue structure with no obvious fibrous encapsulation.

[0048] Figure 27 In Example 25, a comprehensive evaluation of the expression of inflammatory factors in the tissue surrounding the implanted Schlem tube showed that the coating group exhibited a significant reduction in the level of pro-inflammatory factors. Detailed Implementation

[0049] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0050] Example 1 Electrochemical polishing and morphology observation: The surface of the nickel-titanium support was electrochemically polished. After gold sputtering, the morphology was observed by SEM. Figure 1 ).

[0051] Results: After electrochemical polishing, the stent surface exhibited a highly smooth finish, fully meeting the requirements for subsequent processes and clinical use.

[0052] Examples 2-5: Optimization of Alkali Heat Treatment Conditions Example 2 The polished support was ultrasonically cleaned with ethanol and deionized water for 30 min each, and then vacuum dried for 2 h. It was then immersed in a polytetrafluoroethylene liner containing 10 mL of sodium hydroxide solution (14 wt%) at 37 °C for 24 h. After removal, it was soaked in an acidic solution for 2 h to restore the surface to neutral and stabilize the oxide layer structure, then cleaned three times with deionized water and vacuum dried. Finally, the morphology was observed by SEM. Figure 2 ).

[0053] Results: A uniform thin-walled porous network was formed on the surface, with irregularly curved, sheet-like pore walls and uniform pore size. Although this structure has a certain specific surface area, the thin pore walls and moderate porosity limit further improvement in protein loading.

[0054] Example 3 Steps: Same as in Example 2, except the soaking temperature was adjusted to 50℃. Finally, the morphology was observed using SEM. Figure 3 ).

[0055] Results: The surface transformed into a dense structure, with thickened pore walls forming robust stripes, reduced porosity, and localized accumulation. The dense pores hindered deep penetration of the solution, and the uneven distribution of surface roughness was unfavorable for the formation of a uniform protein coating.

[0056] Example 4 Procedure: Same as in Example 2, except the sodium hydroxide concentration was adjusted to 26 wt% and the temperature was 37°C. Finally, the morphology was observed using SEM. Figure 4 ).

[0057] Results: Alkali heat treatment resulted in a highly porous honeycomb network on the surface, with slender pore walls and sharp skeletal edges. This unique topology provides the maximum specific surface area, which is conducive to the penetration and self-polymerization of mussel adhesive proteins into the pores. The sharp edges enhance the mechanical interlocking effect, resulting in a tight bond with the pore walls and significantly improving the adhesion of the coating.

[0058] Example 5 Steps: Same as in Example 2, except the sodium hydroxide concentration was adjusted to 26 wt% and the temperature was 50°C. Finally, the morphology was observed using SEM. Figure 5 ) Results: The surface exhibits a loose fibrous network with needle-like or fibrous pore walls. The pores are sparsely and irregularly distributed, with localized collapses. Due to the weak structural stability and lack of continuous channels, the mussel adhesive proteins cannot form effective anchoring, easily leading to coating peeling.

[0059] Comparing the surface morphology of Examples 2 to 5, it can be seen that Example 4 (26 wt% sodium hydroxide, 37°C) can obtain the most ideal high-porosity honeycomb network, which has both high specific surface area and excellent structural stability. Therefore, it is the preferred substrate treatment scheme for subsequent experiments.

[0060] Examples 6 to 9: Optimization of Mussel Adhesive Protein Pre-deposition Concentration Example 6 Procedure: The porous scaffold (prepared in Example 4) was immersed in 5 mL of mussel adhesive protein solution (0.25 mg / mL) and reacted at room temperature for 2 h. After washing and drying, the sample was observed by SEM. Figure 6 ).

[0061] Result: Sparse granular deposits formed on the surface, with poor uniformity and insufficient coverage.

[0062] Example 7 Procedure: Same as in Example 6, except the concentration of the mussel adhesive protein solution was adjusted to 0.5 mg / mL. SEM observation ( Figure 7 ).

[0063] Results: The surface formed a directional coarse stripe morphology, which was completely encapsulated and highly uniform, and the film was continuous and dense. Example 8 Procedure: Same as in Example 6, except the concentration of the mussel adhesive protein solution was adjusted to 0.75 mg / mL. SEM observation ( Figure 8 ).

[0064] Results: The surface exhibited a fine striped morphology with good uniformity, but the film layer thickened and localized accumulation occurred.

[0065] Example 9 Procedure: Same as in Example 6, but adjust the concentration of the mussel adhesive protein solution to 1.0 mg / mL. SEM observation ( Figure 9 ).

[0066] Results: The surface tends to be near-planar and smooth, with the best uniformity, but the excessive thickness of the film layer leads to the loss of porous structure.

[0067] By comparing the modification effects at different concentrations, Example 7 (0.5 mg / mL) was determined to be the optimal process. The directional coarse stripe morphology formed at this concentration exhibited both excellent uniformity and moderate film thickness, achieving complete encapsulation while preserving the porous characteristics of the substrate to the greatest extent possible. Therefore, the process parameters of Example 7 were selected as the final pretreatment conditions.

[0068] Examples 10 to 12: Optimization of the mussel adhesive protein / bivalirutin coating ratio Example 10 Procedure: The scaffold pre-deposited mussel adhesive protein (Example 7) was immersed in 5 mL of a mixed solution (0.5 mg / mL mussel adhesive protein + 0.25 mg / mL bivalirutin, pH 8.0) and reacted at room temperature for 2 h. After washing and drying, the sample was observed by SEM. Figure 10 ).

[0069] Result: A uniform granular film was formed on the surface. This formulation achieved initial drug coverage and constructed a basic particle packing structure.

[0070] Example 11 Steps: The operating steps in this embodiment are the same as in Example 10, except that the concentration of bivalirutin is adjusted to 0.5 mg / mL (mass ratio 1:1). After preparation, the coating morphology is observed by SEM. Figure 11 A).

[0071] Results: Based on the granular uniform film, the particles are more densely packed and more evenly distributed. At the same time, fiber connections and local film-like regions initially appear on the surface, forming a composite morphology of "particle-fiber-film" coexistence, which significantly improves the density and adhesion of the coating.

[0072] Furthermore, a coating was prepared on the surface of the scaffold according to the method described in this embodiment (Example 11), and its SEM morphology was observed. Figure 11 B).

[0073] Example 12 Procedure: Same as in Example 10, but adjust the bivalirutin concentration to 0.75 mg / mL. SEM observation ( Figure 12 ).

[0074] Results: Based on the granular homogeneous film, the film-like regions significantly expanded and merged into sheets. Although the coating coverage was good, excessively thick continuous film layers may lead to decreased coating flexibility and potentially affect drug release kinetics.

[0075] The optimal preparation ratio of mussel adhesive protein (0.5 mg / mL) + bivalirutin (0.5 mg / mL) was determined. Example 11, while maintaining a uniform and tightly packed particle arrangement, appropriately introduced fibrous and membrane structures, avoiding both the loose structure at low concentrations and the risks associated with excessively thick membranes at high concentrations. Therefore, the treatment conditions of Example 11 were selected for subsequent performance evaluation experiments.

[0076] Example 13 To accurately determine the loading and release behavior of each component in the coating, quantitative detection methods for mussel adhesive protein and bivalrutin were established. Mussel adhesive protein standard curve: The UV-Vis method (280 nm) showed good linearity in the concentration ranges of 25 / 50 / 75 / 100 µg / mL. Figure 13 Bivalirutin standard curve: High-performance liquid chromatography (HPLC) at 220 nm showed good linearity in the concentration range of 20 / 50 / 100 / 200 µg / L. Figure 14 ).

[0077] Example 14 In vitro drug release performance evaluation: The coated sample (Example 11) was placed in 5 mL PBS buffer (pH 7.4, 37℃, 100 rpm). The buffer was completely replaced at 6 h, 12 h, and days 1-7. The concentrations of mussel adhesive protein and bivalrutin were determined by UV-Vis and HPLC, respectively, and the cumulative release curves were plotted. Figure 15 ).

[0078] Results: By day 7, the cumulative release of mussel adhesive protein and bivalirutin reached 163.0 µg / cm² and 124.2 µg / cm², respectively. The coating achieved continuous and simultaneous release of the two drugs within 7 days, demonstrating good long-acting drug release performance.

[0079] Example 15 In vitro hemolytic performance evaluation: Rabbit whole blood was washed with PBS to prepare a 2% red blood cell suspension. The coating from Example 11 (MAP) was then applied. 0.5 / Biva 0.5 ) was co-incubated with 0.5 mL of red blood cell suspension (37℃, 1 h), centrifuged, and the absorbance of the supernatant at 540 nm was measured and the hemolysis rate was calculated. Figure 16 ).

[0080] Results: The hemolysis rate of the coated samples was <5.0%. This indicates that the coating has excellent blood compatibility and is in a safe state with no risk of hemolysis.

[0081] Example 16 Cytotoxicity evaluation: The coating of Example 11 (MAP) was applied at a ratio of 6 cm² / mL. 0.5 / Biva 0.5 Extraction was performed in DMEM for 24 h to obtain the extract. Human corneal epithelial cells (5 × 10³ cells / well) were seeded in 96-well plates and adhered for 24 h. The plates were then replaced with the coated extract and cultured for another 24 h (pure DMEM was used as a negative control). After incubation with CCK-8 reagent for 2 h, the absorbance at 450 nm was measured, and the relative cell viability was calculated. Figure 17 ).

[0082] Results: Cell viability was close to 100%, with no significant difference compared to the negative control group. This indicates that the coating is not cytotoxic to human corneal epithelial cells and maintains good cell viability and biocompatibility.

[0083] Example 17 In vitro anticoagulant activity evaluation: Rabbit whole blood (3.8% sodium citrate anticoagulant, volume ratio 1:9) was centrifuged to prepare platelet-rich plasma. The platelet-rich plasma (PRP) was coated using the method described in Example 11. 0.5 / Biva 0.5 Place the sample at 37°C and add 0.1 mL of plasma for preheating for 3 min. Then add APTT reagent and CaCl2, or TT reagent respectively. Measure the activated partial thromboplastin time (APTT) and thrombin time (TT) using an automated coagulation analyzer. Each group is repeated three times, and the average value is taken. Figure 18 ).

[0084] Results: Compared with the blank control group, the APTT and TT of the coated group were significantly prolonged (prolongation value ≥300 s, p<0.001), reaching the upper limit of detection. This indicates that the coating can be instantly activated and strongly inhibited in vitro, exhibiting significant anticoagulant activity.

[0085] Example 18 Platelet adhesion and morphology observation: Preparation of rabbit platelet-rich plasma (PRP). The platelet-rich plasma (MAP) of Example 11 was coated... 0.5 / Biva0.5 Platelets were placed in 24-well plates, preheated to 37°C, and incubated with 0.5 mL of PRP for 1 h. After washing with PBS, fixing with 2.5% glutaraldehyde (overnight at 4°C), dehydrating with graded ethanol, and sputtering with gold, platelet adhesion morphology was observed using SEM. Figure 19 ).

[0086] Results: The coated surface exhibited extremely low platelet adhesion, with only a few scattered spherical platelets observed, and no pseudopodia extension or aggregation. Compared with the blank control group (which showed extensive spreading and clustering), the number of adherent platelets was reduced by >90%. This indicates that the coating can significantly inhibit platelet activation and aggregation, and possesses excellent immediate antithrombotic ability.

[0087] Example 19 Whole blood adhesion evaluation: Heparin-anticoagulated rabbit whole blood was collected. The coating from Example 11 (MAP) was applied... 0.5 / Biva 0.5 The sample was placed in a 24-well plate, and 1 mL of whole blood was added and incubated at 37°C for 1 h. After washing with PBS, fixation with glutaraldehyde, dehydration, and gold sputtering, the adhesion of whole blood was observed by SEM. Figure 20 ).

[0088] Results: The coated surface remained clean and smooth, with almost no whole blood adhesion. Compared with the blank control group (extensive blood cell spreading and aggregation), the number of adhesions was reduced by >95%. This indicates that under physiological blood flow simulation conditions, the coating exhibits significant anticoagulant and antithrombotic properties, effectively blocking the formation pathway of acute thrombosis.

[0089] Example 20 ROS removal capability evaluation: The coating of Example 11 (MAP) was used to evaluate the ROS removal capability. 0.5 / Biva 0.5 The sample was placed in a 24-well plate, and 100 μM H2O2 solution was added and incubated at 37°C for 30 min to induce oxidative stress. After discarding the reaction solution, 10 μM DCFH-DA probe was added and stained in the dark for 30 min. The sample was then gently washed with PBS to minimize background signal. The fluorescence intensity was observed and recorded using a fluorescence microscope (excitation / emission wavelengths: 488 / 525 nm). Figure 21 ).

[0090] Results: Compared with the untreated group, the fluorescence signal of the coated group was significantly reduced, indicating a substantial decrease in ROS levels in the intracellular or local environment. This demonstrates that the coating has excellent ROS scavenging performance, effectively alleviating oxidative stress damage and maintaining the homeostasis of the local microenvironment.

[0091] Example 21 Rat femoral artery stent implantation experiment and in vivo antithrombotic evaluation: Male SD rats weighing 300-350 g were selected and anesthetized intraperitoneally with 3% sodium pentobarbital (40 mg / kg) after fasting for 12 hours. The right femoral artery (approximately 1 cm long) was dissected under aseptic conditions, and after temporary occlusion of blood flow, MAP was implanted. 0.5 / Biva 0.5 Coated stents (Example 11) and bare metal stents were compared. End-to-end anastomosis was performed using 11-0 nylon sutures, and the wound was sutured after confirming blood flow. Postoperatively, penicillin (20,000 U / day) was administered intramuscularly for three consecutive days to prevent infection. Animals were sacrificed 14 days postoperatively, and the stent-containing vessel segment was completely removed. After rinsing with PBS, macroscopic observation was performed (recording intimal color, thrombus formation, and luminal stenosis). Subsequently, samples were fixed with 2.5% glutaraldehyde (overnight at 4°C), dehydrated with graded ethanol, critical point dried, and sputter-coated with gold. SEM was used to compare the surface cleanliness, thrombus deposition, and coating integrity of the two groups of stents. Figure 22 ).

[0092] Results: The intima of the coated stent group remained smooth and patent, with no signs of thrombosis; while the bare stent group showed obvious thrombus adhesion or luminal stenosis. SEM showed that the coated stent opening and surface were clean, exhibiting excellent blood compatibility, with no thrombus deposition hindering tissue repair.

[0093] Example 22 In vivo biocompatibility and inflammatory response evaluation: Eight-week-old male C57BL / 6 mice (20±2 g) were randomly divided into experimental groups (implanted with the MAP coating of Example 11). 0.5 / Biva 0.5 ≥6 mice were included in each group (stent implanted) and a control group (blank metal stent implanted). Under 1.5% isoflurane inhalation anesthesia, a sac was constructed subcutaneously on the back of the mice and the stent was implanted. The mice were fed for 7 days post-surgery. After euthanasia, the stent and surrounding 0.5 cm tissue were harvested, fixed in 4% paraformaldehyde, embedded in paraffin, and sectioned (4 µm). Hematoxylin-eosin (HE) staining was performed to observe inflammatory cell infiltration, tissue edema, and necrosis. Immunohistochemistry (IHC) was used to detect the expression levels of pro-inflammatory factors TNF-α and IL-6 (positive signals appear brownish-yellow). Figure 23 Immunofluorescence (IF): Macrophages were labeled with F4 / 80 antibody (green fluorescence), and the cell nuclei were counterstained with DAPI to assess the degree of macrophage infiltration. Figure 24 ImageJ software was used to calculate the immunohistochemical positive area rate, and statistical difference analysis was performed. p <0.05).

[0094] Results: The tissue surrounding the implant in the coated group maintained a normal physiological state, with no inflammatory response. The positive expression rates of TNF-α and IL-6 in the coated group were significantly lower than those in the control group. The number of F4 / 80 positive macrophages in the coated group was sparse, and no large-scale aggregation or foreign body giant cell reaction was observed. This indicates that MAP... 0.5 / Biva 0.5 The coated scaffold achieved excellent biocompatibility and immune tolerance after implantation in vivo.

[0095] Example 23 Evaluation of the antithrombotic performance of Schlem tube implanted stent: Six-month-old male New Zealand white rabbits were randomly divided into an experimental group (implanted with MAP prepared in Example 11). 0.5 / Biva 0.5 Coated stents and a control group (with blank metal stents) were used. Stents were implanted into Schlem tubes of rabbit eyes under anesthesia. Animals were sacrificed at 2 and 4 weeks post-surgery, and the stents and surrounding tissues were removed. After fixation with 4% paraformaldehyde, gradient dehydration, and gold sputtering, the microstructure and thrombus deposition on the stent surface were observed using SEM. Figure 25 ).

[0096] Results: At 2 and 4 weeks post-procedure, the surface of the coated stent remained clean and smooth, in an effective state free of thrombus and fibrin deposition, with an intact coating structure. Over time (especially at 4 weeks), significant fibrin adsorption and platelet aggregation appeared on the surface of the bare stent, indicating early signs of thrombosis, and the surface roughness increased significantly.

[0097] Example 24 Histopathological evaluation of Schlem tube implanted scaffolds: Based on the above animal model, ocular tissue blocks containing the scaffolds were obtained at 2 and 4 weeks postoperatively. Hard tissue sections were prepared and stained with hematoxylin and eosin (HE). Inflammatory cell infiltration, fibrous capsule formation, and tissue ingrowth around the scaffolds were observed under a light microscope. Figure 26 ).

[0098] Results: In the untreated group, a small amount of inflammatory cell infiltration was observed around the stent, and a dense, mature fibrous capsule formed on the outer surface of the implant. Fibrous tissue ingrowth and neovascularization were observed within the stent ring. In the coated stent, the tissue interface around the stent was clear, with no inflammatory infiltration, no dense fibrous capsule formation, no fibrous tissue ingrowth or neovascularization within the stent ring, and the internal space remained patent. No acute injuries such as necrosis or severe hemorrhage were observed in the adjacent tissues of either the untreated or coated groups.

[0099] Example 25 The regulatory effect of Schlem tube implanted scaffold on local inflammation and angiogenesis factors: Four weeks post-operation, tissue homogenates were prepared from the area surrounding the implant in rabbit eyes from each group. Enzyme-linked immunosorbent assay (ELISA) was used to detect the expression levels of key pro-inflammatory factors (TNF-α, IL-6) and angiogenesis factor (VEGF-A), and statistical analysis was performed using normal eye tissue as a baseline control. Figure 27 ).

[0100] Results: Compared with normal tissue, the levels of TNF-α and IL-6 in the untreated scaffold tissue were significantly increased. p <0.05), and VEGF-A expression level was also significantly upregulated, suggesting the presence of chronic inflammation and pathological angiogenesis; the expression levels of TNF-α, IL-6 and VEGF-A in the coated scaffold tissue were not significantly different from those in normal tissue. p >0.05), all indicators remained at the physiological baseline level, achieving homeostatic regulation of the local microenvironment.

[0101] Attention to all those skilled in the art: Although the present invention has been described according to the specific embodiments above, the inventive concept of the present invention is not limited thereto. Any improvements utilizing the inventive concept will be included within the scope of protection of this patent. The above descriptions are merely preferred embodiments of the present invention, and the scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the inventive concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principle of the present invention should also be considered within the scope of protection of the present invention.

Claims

1. A stent for drainage of aqueous humor in anticoagulated glaucoma, characterized in that: The scaffold body includes a nickel-titanium scaffold body, the surface of which is sequentially electrochemically polished and alkaline thermally treated to form an activated surface with a porous structure; on the activated surface, a mussel adhesive protein pre-deposited bottom layer and a mussel adhesive protein / bivarutin functional surface layer are sequentially loaded; wherein, the mussel adhesive protein / bivarutin functional surface layer is formed by co-depositing a mixed solution of mussel adhesive protein and bivarutin at a mass ratio of 1:

1.

2. The intra-aqueous drainage stent for anticoagulation glaucoma according to claim 1, characterized in that, In the mixed solution that forms the mussel adhesive protein / bivalirutin functional surface layer, the mass concentration of both mussel adhesive protein and bivalirutin is 0.5 mg / mL.

3. A method for preparing an anticoagulation glaucoma aqueous humor drainage stent as described in any one of claims 1 to 2, characterized in that, Includes the following steps: S1. Electrochemical polishing: The nickel-titanium support is immersed in phosphoric acid solution and polished by passing a direct current for 15-20 min. Then, the support is ultrasonically cleaned with anhydrous ethanol and deionized water in sequence for a total cleaning time of 30 min. Finally, it is vacuum dried for 2 h to remove surface processing defects and the original oxide layer. S2, Alkali heat treatment: The scaffold polished in step S1 is immersed in sodium hydroxide solution for 24 hours, then taken out and rinsed with deionized water 3 times; then immersed in dilute acid solution for 2 hours to neutralize the residual alkali on the surface and regenerate the oxide layer; finally rinsed with deionized water until neutral and vacuum dried to form a nanoporous structure rich in hydroxyl groups on the surface of the scaffold. S3. Construction of mussel adhesive protein pre-deposition layer: Mussel adhesive protein is dissolved in buffer solution to prepare pre-deposition solution; the scaffold treated in step S2 is completely immersed in the pre-deposition solution and allowed to stand at room temperature for 2 h to react. Mussel adhesive protein pre-deposition layer is formed on the surface of the scaffold by utilizing the coordination of dopa groups of mussel adhesive protein with the metal surface. S4. Co-deposition of mussel adhesive protein / bivalutine coating: Mussel adhesive protein and bivalutine are dissolved in buffer solution at a mass ratio of 1:1 to prepare a mixed deposition solution. The mass concentration of both mussel adhesive protein and bivalutine in the mixed solution is 0.5 mg / mL. The scaffold with pre-deposited substrate obtained in step S3 is transferred to the mixed deposition solution and allowed to stand at room temperature for 2 h. This immersion process is repeated 2-3 times. After each immersion, the scaffold is removed, cleaned, and dried until a uniform mussel adhesive protein / bivalutine functional surface layer is formed on the substrate surface. S5. Post-treatment and finished product preparation: The coated support obtained in step S4 is washed in deionized water for 24 h to remove unbonded free components, and then vacuum dried at 37°C for 24 h or freeze-dried to obtain the finished product.

4. The preparation method according to claim 3, characterized in that, In step S1, the concentration of the phosphoric acid solution is 10 wt%, the solution temperature during polishing is 60 °C, and the current density is 0.5-1.5 A / dm².

5. The preparation method according to claim 3, characterized in that, In step S2, the concentration of the sodium hydroxide solution is 14-26 wt%, and the treatment temperature is 37-50℃.

6. The preparation method according to claim 3, characterized in that, In step S2, the dilute acid solution is a dilute hydrochloric acid solution with a concentration of 0.01-0.1 mol / L.

7. The preparation method according to claim 3, characterized in that, In step S3, the concentration of the mussel adhesive protein solution used to construct the pre-deposited bottom layer is 0.25-1.0 mg / mL; the buffer solution is 10 mM Tris-HCl buffer with a pH of 8.

0.

8. The preparation method according to claim 3, characterized in that, In step S4, the solvent for the mixed deposition solution used for co-deposition of the surface layer is 10 mM Tris-HCl buffer with a pH of 8.0; the mass concentrations of mussel adhesive protein and bivalirutin in the solution are both 0.5 mg / mL.

9. The application of the anticoagulation glaucoma aqueous humor drainage stent as described in claim 1 in the preparation of ophthalmic antithrombotic and anti-inflammatory materials.

Citation Information

Patent Citations

  • Intravascular stent based on mussel mucin coating and preparation method of intravascular stent

    CN107308507A

  • Artificial aqueous humor micro-drainage tube with drug sustained release function and preparation method of artificial aqueous humor micro-drainage tube

    CN114129769A